Protective clothing for pesticide operators: part II – data analysis of fabric characteristics. Issue 1 (2nd January 2016) - Shaw, Anugrah; Schiffelbein, Paul
Abstract : Development of objective measurements is an important requirement for establishing performance-based standards for protective clothing used while handling pesticide. This study, the second in a two-part series, reports on the work completed to evaluate the performance of approximately 100 fabrics that are either used or have the potential to be used for garments worn by operators while applying pesticides. Part I, published separately, provides an overview of these issues and describes research undertaken to select a test chemical for use in subsequent studies. The goals of this study were first to develop a comprehensive approach to evaluate the performance of garments currently being used by pesticide operators, and second, to use the laboratory and field data in the development of performance specifications.